1990
DOI: 10.1126/science.1971458
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid β Protein Precursor Gene and Hereditary Cerebral Hemorrhage with Amyloidosis (Dutch)

Abstract: Human hereditary cerebral hemorrhage with amyloidosis of the Dutch type (HCHWA-D), an autosomal dominant form of cerebral amyloid angiopathy (CAA), is characterized by extensive amyloid deposition in the small leptomeningeal arteries and cortical arterioles, which lead to an early death of those afflicted in their fifth or sixth decade. Immunohistochemical and biochemical studies have indicated that the amyloid subunit in HCHWA-D is antigenically related to and homologous in sequence with the amyloid beta prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
220
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(226 citation statements)
references
References 28 publications
(19 reference statements)
5
220
0
1
Order By: Relevance
“…Familial forms of AD result from a single point mutation in A␤ peptides and are characterized by early onset and aggravated severity. In this article, we focus on the Dutch AD type, which is associated with the E22Q substitution (21). Numerous in vitro experiments have shown that A␤ peptides with the Dutch mutation aggregate more readily than their WT A␤ counterparts, in addition to exhibiting increased cytotoxic activity (1,3,22).…”
Section: Discussionmentioning
confidence: 99%
“…Familial forms of AD result from a single point mutation in A␤ peptides and are characterized by early onset and aggravated severity. In this article, we focus on the Dutch AD type, which is associated with the E22Q substitution (21). Numerous in vitro experiments have shown that A␤ peptides with the Dutch mutation aggregate more readily than their WT A␤ counterparts, in addition to exhibiting increased cytotoxic activity (1,3,22).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional peaks corresponding to A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) were also observed, although they were substantially smaller than the A␤(1-10) peak. When A␤(1-28) was incubated with BACE2, pronounced peaks corresponding to A␤(1-19) and A␤(1-20) were observed, as was A␤(21-28), the C-terminal counterpart of A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)…”
Section: Bace2 Generates Two C-terminal Fragments Of Appmentioning
confidence: 99%
“…The same peptide incubated with BACE1 produced a strong peak corresponding to the A␤(1-10) and a peak corresponding to A␤ (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) consistent with the observed internal A␤ cleavage product after Tyr-10 (15). Two additional peaks corresponding to A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and A␤ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)…”
Section: Bace2 Generates Two C-terminal Fragments Of Appmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic mutations within the A␤ peptide sequence have been reported, including the Flemish (A21G) (27), Italian (E22K) (28), Dutch (E22Q) (29,30), Arctic (E22G) (31), and Iowa (D23N) (32,33) mutations. Clinically, these mutations lead to AD-like symptoms secondary to intracerebral hemorrhage, although in some cases a progressive dementia is present in the absence of stroke.…”
mentioning
confidence: 99%